Local coloring of self complementary graphs - P. Deepa; P. Srinivasan; M. Sundarakannan (AKCE International Journal of Graphs and Combinatorics, 2017)
Let be a graph. A local coloring of a graph of order at least 2 is a function having the property that for each set with , there exist vertices such that , where is the size of the induced subgraph . The maximum color assigned by a local coloring to a vertex of is called the value of and is denoted by . The local chromatic number of is , where the minimum is taken over all local colorings of . In this paper we study the local coloring for some self complementary graphs. Also we present a sc-graph with local chromatic number for any given integer .